Penerapan Teknik Pernapasan Buteyko Terhadap Penurunan Gejala Asma Bronkhiale di Puskesmas Kota Garo Kampar Riau Tahun 2025 - Yasfinarti (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Objective: To analyze the effectiveness of the Buteyko breathing technique in reducing symptoms of bronchial asthma. Methods: The study used a quasi-experimental design with a non-random control group pretest-posttest approach. The sample consisted of 20 respondents selected through total sampling. Data were collected using the Asthma Control Test (ACT) questionnaire and direct observation of breathing pattern changes before and after the intervention. Results: Prior to the intervention, 70% of respondents had uncontrolled asthma. After the intervention, 80% of respondents had well-controlled asthma and 5% had completely controlled asthma. Statistical analysis showed a significant effect of the Buteyko breathing technique in reducing asthma symptoms (p-value = 0.000). Conclusion: The Buteyko breathing technique is effective in reducing symptoms of bronchial asthma and can be used as a complementary therapy in the management of bronchial asthma in primary health care. It is recommended that health workers integrate this technique into asthma treatment strategies.